2020
DOI: 10.3390/geosciences10060237
|View full text |Cite
|
Sign up to set email alerts
|

Nature Does the Averaging—In-Situ Produced 10Be, 21Ne, and 26Al in a Very Young River Terrace

Abstract: The concentrations of long-lived in-situ produced cosmogenic nuclides (10Be, 21Ne, 26Al) in quartz obtained from a very recent (~200 a; based on 14C data on organic material) terrace of the Swakop River in Namibia are nearly constant throughout a 322 cm-long depth profile. These findings corroborate earlier hypotheses postulating a homogeneous distribution of these nuclides in freshly deposited river terrace sediments. An averaged nuclide concentration is a crucial and generally assumed prerequisite for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…(5) The rivers east of the Great Escarpment and south of Windhoek run to the south or southeast until they reach the Orange River that flows west to terminate in the Atlantic Ocean (Strohbach 2008). Palaeoclimate proxies for the past 2000 years seem to indicate relatively humid conditions for the last two centuries (Burrough and Thomas 2013;Nash et al 2016), which is in line with an increased number of floods in the same time (Greenbaum et al 2014) and may result in a comparatively high amount of stochastically occurring modern fluvial sediment transport (Gärtner et al 2020).…”
Section: Known Patterns Of Sedimentary Fluxes In Southern Africamentioning
confidence: 87%
“…(5) The rivers east of the Great Escarpment and south of Windhoek run to the south or southeast until they reach the Orange River that flows west to terminate in the Atlantic Ocean (Strohbach 2008). Palaeoclimate proxies for the past 2000 years seem to indicate relatively humid conditions for the last two centuries (Burrough and Thomas 2013;Nash et al 2016), which is in line with an increased number of floods in the same time (Greenbaum et al 2014) and may result in a comparatively high amount of stochastically occurring modern fluvial sediment transport (Gärtner et al 2020).…”
Section: Known Patterns Of Sedimentary Fluxes In Southern Africamentioning
confidence: 87%
“…Prolonged sediment residence times, together with complex sedimentary dynamics in large rivers (Gärtner et al., 2020), lead to downstream signal attenuation. The implication of which is the dampening of the signal of climatic cycles (as well as uncommon short‐term, <10 5 yr, tectonic events) on rates of weathering recorded in sedimentary archives.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of mineral inclusions which have U and Li concentrations comparable to or below those of the host phase might not present a problem for determining 3 He concentrations. Gayer et al (2004), for instance, found no difference in the 3 He concentration between garnet aliquots with many ilmenite inclusions and those with fewer inclusions. Ilmenite has neither high U nor Li concentrations; therefore, it would not significantly contribute to the overall 3 He concentration.…”
Section: Source Of Excess 3 He From Inclusionsmentioning
confidence: 96%
“…They also found that the chemical composition, mainly Ti substitution for Fe and associated phase changes, had no effect on the cosmogenic 3 He production rate. Matsumura et al (2014) measured concordant 10 Be, 36 Cl, and 3 He exposure ages in magnetite, but reported high 26 Al and 21 Ne concentrations due to silicate inclusions. This observation highlights the contribution of frequently present inclusions within the magnetite, which can potentially increase the measured concentration of cosmogenic nuclides.…”
Section: Introductionmentioning
confidence: 99%